Comparing four heat-inducible promoters in stably transformed sugarcane regarding spatial and temporal control of transgene expression reveals candidates to drive stem-preferred transgene expression - Qiande, Moni; Altpeter, Fredy (Frontiers in Plant Science, 2025)
Small heat shock protein (sHSP) promoters contain cis-regulatory elements that facilitate transcription in response to heat stress, making them valuable tools for functional studies through controlled gene expression and the precise regulation of gene-editing tools or morphogenic regulators. To evaluate their utility, GUS reporter gene expression driven by four plant-sourced HSP promoters (pGmHSP17.5, pHvHSP17, pZmHSP17.7, and pZmHSP26) was compared across various tissues of stably transformed sugarcane before and after heat treatment. At 22°C, all promoters showed minimal activity in leaves and roots, although pZmHSP17.7 and pHvHSP17 displayed moderate expression in stems. Following heat treatment, all promoters exhibited their highest activity in stems, followed by leaves and roots. In stem tissues, pGmHSP17.5 displayed heat-induced uidA expression comparable to the constitutive pZmUbi promoter. Notably, heat-induced reporter gene activity in stem middle sections of single-copy transgenic lines containing pZmHSP17.7, pHvHSP17, or pZmHSP26 exceeded pZmUbi-derived uidA activity by 9.7-fold, 3.8-fold, and 3.0-fold, respectively, with 346- to 3,672-fold induction compared to control conditions. Most promoters showed peak expression in the middle sections of the stem, while pHvHSP17 was the most active in the stem apices. Histochemical analysis revealed that pZmHSP17.7 and pHvHSP17 were active in both parenchyma cells and vascular bundles within sugarcane stems. Among leaf tissues, mature leaves exhibited greater expression than senescing or immature leaves, while root activity remained consistently minimal across all promoters. Temperature-course experiments identified distinct activation thresholds: 34°C–36°C for pZmHSP17.7, 36°C for pZmHSP26, 36°C–38°C for pHvHSP17, and 40°C–42°C for pGmHSP17.5. Drought stress also induced reporter gene transcription in stems under HSP promoters, although with lower fold induction than heat treatment. These findings provide valuable tools for gene function studies and biotechnology applications, including heat stress tolerance research, controlled transgene expression in metabolic engineering, precision gene editing, and developmental biology studies.